Bruton’s tyrosine kinase activity is negatively regulated by Sab, the Btk-SH3 domain-binding protein - Yamadori, Tomoki (The National Academy of Sciences, 1999)
Bruton’s tyrosine kinase (Btk) is a cytoplasmic tyrosine kinase that is crucial for human and murine B cell development, and its deficiency causes human X-linked agammaglobulinemia and murine X-linked immunodeficiency. In this report, we describe the function of the Btk-binding protein Sab (SH3-domain binding protein that preferentially associates with Btk), which we reported previously as a newly identified Src homology 3 domain-binding protein. Sab was shown to inhibit the auto- and transphosphorylation activity of Btk, which prompted us to propose that Sab functions as a transregulator of Btk. Forced overexpression of Sab in B cells led to the reduction of B cell antigen receptor-induced tyrosine phosphorylation of Btk and significantly reduced both early and late B cell antigen receptor-mediated events, including calcium mobilization, inositol 1,4,5-trisphosphate production, and apoptotic cell death, where the involvement of Btk activity has been demonstrated previously. Together, these results indicate the negative regulatory role of Sab in the B cell cytoplasmic tyrosine kinase pathway.